Bilateral Lower Cervical Bifurcation of the Common Carotid Artery. (31st July 2013) - Uzun, Lokman; Kokten, Numan; Kilicaslan, Adem; Tasel, Bulent; Kalcioglu, M. Tayyar; Tekin, Muhammet
Abstract : Lower cervical bifurcation of cervical common carotid artery (CCA) is a very rarely encountered anatomic variation. Knowing the normal vascular anatomy and also its anomalies is important in preventing the vascular complications. Ill-defined vascular anomalies may lead to massive hemorrhage and eventually death during head and neck surgery. Imaging of the neck by magnetic resonance Imaging (MRI), CT, or angiography is helpful for diagnosis. We present a 62-year-old male patient diagnosed with laryngeal carcinoma who had been treated. His MRI revealed bilateral low-level bifurcation of the cervical common carotid arteries as well as tumor localization and its boundaries. Total laryngectomy and right selective neck dissection was performed to the patient with the diagnosis of squamous cell carcinoma of the larynx. During the neck dissection, carotid bifurcation was detected in common border of Level 3 and Level 4 of the neck.